Hypercalcemia: An Unusual Manifestation of Uterine Leiomyoma. (12th February 2013) - Garcha, Amarinder Singh; Gumaste, Purva; Cherian, Sujith; Khanna, Apurv
Abstract : We present a case of hypercalcemia in a 79-year-old female likely secondary to uterine leiomyoma. To the best of our knowledge, hypercalcemia due to a benign tumor has only been described in five cases. Of these above five cases, uterine leiomyoma was thought to be the cause of hypercalcemia in three cases.